CIVIL RESPONSIBILITY AND DANGEROUS ACTIVITIES FROM THE NONCONTRACTUAL DAMAGE - Sevdai Morina (European Scientific Journal, ESJ, 2015)
Apart from the subjective responsibility on causing damage and its compensation there exist also the objective responsibility, respectively responsibility for goods for dangerous activities. This type of responsibility is connected with the XX Century with the appearance of new technical discoveries, discoveries of new and complicated machines and with the massive development of technic perfection in the land, water and the air traffic. As a consequence of this, damages are more frequent and always bigger. From these suffer persons that are in direct contact with these means (workers) and also third persons and surroundings that are surrounded by these means. These damages are the consequences of the rapid technologic development. Regarding the subjective responsibility rules of responsibility on guilt are applied in the cases of cause of damage because of personal activities, whereas objective responsibility on these damages, responsible cannot be considered person that commited the act as well as the person that suffered damage. From this it is seen that the rules on responsibility on damage should not be based on guilt. Therefore in the case of damage causing from the dangerous goods, the damage should be verified and the also the causal link between damage and the dangerous goods (pests). In these situations it is not neccessary to conclude and to verify the guilt of pest. This responsibility in the other way is called the responsibility without guilt, responsibility on dangerous goods and dangerous activity or as responsibility based upon the theory of causality. Thus, also for this responsibility from dangerous goods, is named also as the responsibility without guilt.